Literasi Keuangan sebagai Strategi Peningkatan Ketahanan Ekonomi Generasi Muda di Indonesia - Fifi Yanti, Maria; Irhamna, Irhamna; Rauzah, Rauzah; Zia Ulhaq, Anjumi (Economia: Journal of Economics and Management, 2025)
The low level of financial literacy among young people in Indonesia poses a significant challenge that may affect their ability to cope with economic uncertainties. This study aims to analyze the role of financial literacy as a strategy to enhance the economic resilience of the younger generation. The research employs a descriptive qualitative approach using a literature study method by reviewing relevant sources, including academic journals, books, and official reports. The findings indicate that financial literacy has a significant influence on financial management behavior, such as saving habits, expenditure control, and long-term financial planning. Furthermore, financial literacy contributes to the development of financial stability, which serves as a foundation for individual economic resilience. However, its effectiveness is influenced by factors such as education, access to information, and social environment. Therefore, systematic efforts are needed to improve financial literacy as a strategic approach to strengthening the economic resilience of young people. Abstrak Rendahnya tingkat literasi keuangan di kalangan generasi muda di Indonesia menjadi permasalahan yang berpotensi memengaruhi kemampuan mereka dalam menghadapi tantangan ekonomi. Penelitian ini bertujuan untuk menganalisis peran literasi keuangan sebagai strategi dalam meningkatkan ketahanan ekonomi generasi muda. Metode yang digunakan adalah pendekatan kualitatif deskriptif melalui studi pustaka dengan mengkaji berbagai sumber literatur yang relevan, seperti jurnal ilmiah, buku, dan laporan resmi. Hasil penelitian menunjukkan bahwa literasi keuangan memiliki pengaruh signifikan terhadap perilaku pengelolaan keuangan, termasuk dalam hal menabung, pengendalian pengeluaran, dan perencanaan keuangan jangka panjang. Selain itu, literasi keuangan berkontribusi dalam membentuk stabilitas finansial yang mendukung ketahanan ekonomi individu. Namun, efektivitasnya dipengaruhi oleh faktor pendidikan, akses informasi, dan lingkungan sosial. Oleh karena itu, diperlukan upaya sistematis untuk meningkatkan literasi keuangan guna memperkuat ketahanan ekonomi generasi muda.